PENGARUH INTELEKTUAL KAPITAL, STRUKTUR MODAL, DAN TATA KELOLA PERUSAHAAN TERHADAP NILAI PERUSAHAAN - Rosada, Amrina; Hertati, Lesi; Munandar, Aris (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2025)
The company's value is a performance indicator displayed in the form of stock prices formed by the supply and demand in the capital market, representing society's assessment of the company's performance. This research aims to examine the influence of intellectual capital, capital structure, and corporate governance on the company's value. This study is a quantitative descriptive type, with data sourced from the distribution of questionnaires. A total of 40 respondents were successfully gathered by distributing questionnaires to employees of PT. Telaga Hikmah Ogan Komering Ilir, South Sumatra, Indonesia. This research used purposive sampling technique. The analysis technique employed was quantitative analysis based on the questionnaire distribution results. The analysis results indicate that individually, with a significance value (sig) of intellectual capital (0.014), capital structure (0.001), and corporate governance (0.001) each has a positive and significant effect on the increase in company value with a value (prob < alpha = 0.05). Furthermore, simultaneously, the intellectual capital, capital structure, and corporate governance variables together have a positive impact on the increase in company value (prob < alpha = 0.05).